Soil Surfactant Products for Improving Hydrologic Function in Post‐Fire Water‐Repellent Soil. Issue 5 (20th September 2013) - Madsen, Matthew D.; Coronel, Eric G.; Hopkins, Bryan G.
Abstract : There is a wide range of soil surfactant chemistries on the market today that are primarily designed for the treatment of water‐repellent soils in cropping and turfgrass systems. These chemicals may also have potential in treating the deleterious effects associated with post‐fire water‐repellent soils. The objective of this study was to compare 13 commercially available soil surfactant products with regard to their ability to influence water penetration and soil water‐holding capacity in post‐fire water‐repellent soil. The impact of the surfactant on soil water penetration and water‐holding capacity was determined through water drop penetration time tests and laboratory column infiltration experiments, respectively. All products evaluated in the study improved water penetration and generally increased soil water retention; however, the degree of performance varied widely among products. Irrigaid Gold, Advantage, Penn Wetting, Pervaide, and Tournament Ready were typically the most effective at treating soil water repellency. Hydro Wet, Intake, Attain FC, Wet‐Sol Gro, and EZ Wet in general showed an intermediate response, while Fulmax, PenaTron, and Penex were less effective than the other products. We assume that the products that had the greatest improvements in water penetration and retention will also be the most effective in restoring hydrologic function of post‐fire water‐repellent soils; however, the full utility of the products was not demonstrated in this study, particularly with respect to plant growth. Additional laboratory and field studies are merited for understanding how these different surfactant chemistries influence revegetation success.